2019
DOI: 10.1103/physrevx.9.031047
|View full text |Cite
|
Sign up to set email alerts
|

Spin Excitations of a Proximate Kitaev Quantum Spin Liquid Realized in Cu2IrO3

Abstract: Magnetic moments arranged at the corners of a honeycomb lattice are predicted to form a novel state of matter, the Kitaev quantum spin liquid, under the influence of frustration effects between bond-dependent Ising interactions. Some layered honeycomb iridates and related materials, such as Na 2 IrO 3 and α-RuCl 3 , are proximate to the Kitaev quantum spin liquid, but bosonic spin-wave excitations associated with undesirable antiferromagnetic long-range order mask the inherent properties of the Kitaev Hamilton… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 59 publications
8
42
0
Order By: Relevance
“…High-quality polycrystalline samples of Cu 2 IrO 3 were prepared by a low-temperature topotactic reaction of Na 2 IrO 3 with CuCl as reported previously [32]. Powder x-ray diffraction confirmed the expected crystal structure (C2/c space group), and ac and dc susceptibility measurements down to 300 mK (Appendix A) confirmed the absence of spin freezing, which has been reported to contaminate the lowtemperature magnetism for some Cu 2 IrO 3 materials reported previously [31,34].…”
Section: Experimental Methodssupporting
confidence: 54%
See 2 more Smart Citations
“…High-quality polycrystalline samples of Cu 2 IrO 3 were prepared by a low-temperature topotactic reaction of Na 2 IrO 3 with CuCl as reported previously [32]. Powder x-ray diffraction confirmed the expected crystal structure (C2/c space group), and ac and dc susceptibility measurements down to 300 mK (Appendix A) confirmed the absence of spin freezing, which has been reported to contaminate the lowtemperature magnetism for some Cu 2 IrO 3 materials reported previously [31,34].…”
Section: Experimental Methodssupporting
confidence: 54%
“…In particular, despite a Curie-Weiss temperature and effective magnetic moment similar to Na 2 IrO 3 , muon spin relaxation (μSR) and specific heat studies on Cu 2 IrO 3 have shown an absence of magnetic order and an excitation spectrum dominated by low-energy Ir spin dynamics [32,33]. The correlated nature of this low-temperature dynamic paramagnet is further supported by the nuclear quadrupole resonance (NQR) measurements [34]. These findings suggest that Cu 2 IrO 3 may offer an ideal playground to investigate fractionalization in a Kitaev QSL with an eye towards positive characterization of the Majorana fermions therein.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A similar trend is observed in Figure 6 b for the first-generation material Na IrO that shows a peak at K and its second-generation counterpart Cu IrO that does not show a peak but seems to have a broad anomaly below 5 K. Neutron scattering experiments have confirmed a zigzag AFM order in Na IrO [ 39 ]. Recent SR and NMR experiments have revealed a coexistence of static and dynamic magnetism below 5 K in Cu IrO but without a long-range order, suggesting proximity to the QSL phase [ 25 , 40 ].…”
Section: Magnetic Characterization Of Metastable Kitaev Materialsmentioning
confidence: 99%
“…The unique properties of quantum spin liquids have attracted much research interest [6][7][8], in particular for their emergent Majorana physics [9] and their long-standing relation with unconventional superconductivity [10,11]. A variety of compounds showing quantum spin-liquids physics have been identified [12][13][14][15][16][17][18][19][20][21][22], including the gapless triangular lattice Dirac quantum spin-liquid in NaYbO 2 [23,24] and different van der Waals materials [25][26][27][28]. Interestingly, finding gapless Dirac spin liquids in van der Waals materials would provide a spinon version of graphene Dirac electrons, opening the door to explore strain gauge fields in spinons [29][30][31], spinon flat bands by twist engineering [32][33][34][35], and impurityinduced spinon resonances [36,37].…”
Section: Introductionmentioning
confidence: 99%